For me, it’s easiest when i distribute the negative sign if i need to and then reorder to put the like terms together. and then solve.
(also sorry if it’s a little confusing with all the parentheses, i use them because it helps me organize everything)
21. (4x-9y) + (6x+10) + (8y-4)
= 4x + 6x - 9y + 8y + 10 - 4
= 10x - y + 6
—> D
22. (6x+9y-15) + (2x-9y+8)
= 6x + 2x + 9y - 9y - 15 + 8 (the 9y - 9y = 0, so you can leave it out of the final equation)
= 8x - 7
—> D
23. (9x^2-8x+3) - (5x^2-6x+4)
= 9x^2 - 8x + 3 - 5x^2 -(-6x) - 4
= 9x^2 - 5x^2 - 8x + 6x + 3 - 4 (remember that two - signs next to each other make a + sign)
= 4x^2 - 2x - 1
—> A
24. (9x^3-7x+8) - (5x^2+7x-10)
= 9x^3 - 7x + 8 - 5x^2 - 7x -(-10)
= 9x^3 - 5x^2 - 7x - 7x + 8 + 10
= 9x^3 - 5x^2 - 14x + 18
—> D
25. (6x+14y) - ((7x+5y) + (x-8y))
= (6x+14y) - (7x + x + 5y - 8y)
= (6x+14y) - (8x-3y)
= 6x + 14y - 8x -(-3y)
= 6x - 8x + 14y + 3y
= -2x + 17y
—> B
So pretty much you can get 2 pieces out of each cake with 1/2 left over. Now do this, 2+2+2+2+2=10 now take that 1/2 and do this .5+.5+.5+.5+.5= 2.5 now add that to the 10 and that is your answer
Answer:
s ≤ -18
Step-by-step explanation:
Multiply both sides of the inequality by -3. Since the multiplier is negative, you need to reverse the comparison symbol.
(-3)(-s/3) ≤ (-3)(6)
s ≤ -18
_____
If you multiply by a positive number, you don't need to reverse the symbol. Hence multiplying by 3 gives ...
-s ≥ 18
You can now add s to both sides:
0 ≥ 18 + s
and subtract 18 from both sides:
-18 ≥ s
Of course, this is the same relationship as ...
s ≤ -18
Answer:
163 - p = 291
Step-by-step explanation: